Downed woody debris varies with climate and harvesting treatment in Douglas-fir forests of British Columbia, Canada - Roach, Winnifred Jean; Simard, Suzanne W.; Snyder, Eva N. (Frontiers in Forests and Global Change, 2024)
This manuscript informs and promotes sustainable forest management by identifying harvesting treatments that result in woody debris characteristics that are ecologically desirable and promote biodiversity. The manuscript fits into the specialty topic because woody debris dynamics are directly related to forest soils through their influence on nutrient cycling. The manuscript presents data on the differences in woody debris across a climate gradient. The gradient includes warm climates that the cooler sites in the study are likely to transition into.